PENGARUH PERMAINAN PLAYDOUGH TERHADAP KEMAMPUAN MOTORIK HALUS ANAK KELOMPOK B - Martuty, Arie; Intisari; Tasrif Akib; Heni Safitri Hasbur; Arma Suriani (Early Childhood: Jurnal Pendidikan, 2025)
This study aims to determine the effect of playdough games  on the improvement of fine motor skills of group B children at Al-Iman Padi Gantarang Bulukumba Kindergarten. The research method used was an experiment with a pre-test and post-test design  on 12 children as a sample. Data analysis was carried out using the Wilcoxon test to test the difference in scores before and after treatment. The results showed that there was a significant improvement in children's fine motor skills after playing playdough, with the average score increasing from 20.75 to 54.83, suggesting that this game was effective in training children's fine motor skills. In addition, playdough games  also attract children's attention, making the learning process more fun and interactive